EXPLORING FACULTY PERCEPTIONS REGARDING INTEGRATION OF ARTIFICIAL INTELLIGENCE IN MEDICAL AND DENTAL EDUCATION - Ali, Sarah; Aziz, Anbreen; Zahoor, Hina (Journal of Ayub Medical College Abbottabad, 2024)
Background: Considering hype about artificial intelligence, limited research has been done regarding its integration in medical and dental education within Pakistani context. This study aims to explore faculty perceptions on integrating AI into medical and dental education. Methods: This is an exploratory qualitative study that has explored faculty perceptions on integrating Artificial Intelligence into medical and dental education. A purposive sample of 20 faculty members participated in the study. An interview guide with six semi-structured questions was utilized for data collection. After assuring anonymity and confidentiality, all interviews were audio recorded and transcribed verbatim. The transcripts were anonymized and shared with the co-authors for data analysis. Thematic analysis with a deductive approach was performed by utilizing the six-step process provided by Braun and Clarke. Results: Five main themes and fifteen subthemes emerged. The participants said that artificial intelligence has the power to completely transform medical and dental education by enhancing teaching, research and patient care. Some challenges need to be addressed that restrict wide implementation of artificial intelligence in the healthcare sector such as lack of expertise, resource constraints, and lack of understanding to use it for teaching and learning. Artificial intelligence has the potential to improve the learning environment by modifying learning experiences of students. According to the results, Institutions has a responsibility to provide comprehensive training programs for this purpose Artificial intelligence ethics must be kept in mind while integrating it into medical and dental education by creating explicit policies and offering faculty development initiatives. Conclusion: This study highlights the necessity of training programs that allow medical and dental faculty to effectively use artificial intelligence to enhance teaching and practice in healthcare. It is pertinent to keep ethics in mind while utilizing Artificial Intelligence into medical and dental education.